Trudności i szanse wychowania na współczesnym uniwersytecie: autorytet mistrza - Rossa, Piotr (Przedsiębiorstwo Produkcyjno-Handlowe ZAPOL, 2013)
The university as a community of theachers and students is dedicated to the search for truth through scientific research. This search is intrinsically connected with the university's educational role. It is a role which, for centuries, has been bound up with the authority of the academic teacher who is also a mentor. Contemporary transformations have resulted in placing an ever growing emphasis on the student's professional training and a lesser emphasis on educational tasks. The modern university is characterized by an economization and an easy access to multiple fields of study. In spite of a frequent tendency to abandon the task of factual evaluation, the university retains some of its educational functions which are linked with the person who is both a teacher and a mentor, as for instance, in the case of a project coordinator.
Difficulties and opportunities in modern university education: the mentor's authority
Keywords: uniwersytet; wychowanie; autorytet; wspólnota akademicka; prawda; edukacja; academic teacher; mentor; student; transformation; community of teachers and students; university; scientific research; search for truth; educational role; authority; Kraków; Jan Kanty; Stróżewski W.; Uniwersytet Krakowski; Universidad de Cracovia; Cracow university; جامعة كراكو; 克拉科夫大学; クラクフ大学; αλήθεια; クラクフ; 克拉科夫; क्राको; 克拉科夫